PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDENT, KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAN DAN LEVERAGE TERHADAP TAX AVOIDANCE (Studi Kasus Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Anisa Nike Wulandari, 14.05.52.0298; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
The purpose of this study was to examine and analyze the influence of the proportion of independent board, audit committee, institutional ownership, firm size and leverage against tax avoidance in companies listed on the Stock Exchange Year 2013-2015. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in the period 2013- 2015. The sample in this study as many as 55 companies. The sampling technique used purposive sampling. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: The proportion of independent board no significant positive effect on tax avoidance. The Audit Committee significant negative effect on tax avoidance. Institutional ownership has significant negative effect on tax avoidance. Size significant negative effect on tax avoidance. Leverage significant positive effect on tax avoidance.Keywords: The Proportion of Independent Board, Audit Committee, Institutional Ownership, Firm Size, Leverage and Tax Avoidance